Impact of Shopee Skincare Price, Reviews, and Quality on Purchasing Decisions: Pengaruh Harga, Ulasan, dan Kualitas Perawatan Kulit Shopee terhadap Keputusan Pembelian - Rischawati, Novita; Indayani, Lilik; Oetarjo, Mas (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of price, online customer reviews, and electronic service quality on skincare purchasing decisions within the Shopee marketplace, focusing on East Java. Through a quantitative approach involving 96 respondents sampled purposively, data was collected via Google Forms and analyzed using descriptive statistics and multiple linear regression in SPSS. Results indicate significant positive effects of these factors on skincare purchasing decisions. Recommendations are made for Shopee and skincare sellers to enhance pricing strategies, prioritize customer reviews, and improve electronic service quality, aiming to optimize consumer decision-making processes and build trust in online transactions. This research contributes insights tailored to the skincare industry within online marketplaces, particularly in East Java, addressing a notable gap in existing literature. Highlight: Shopee skincare purchasing decisions study, East Java, quantitative analysis. 96 purposive sampled respondents enhance study validity and relevance. Findings: price, reviews, service quality impact skincare buying decisions. Keywoard: Shopee, skincare, purchasing decisions, online marketplace, East Java